12 (N\T@DOW(B. (NSO^(B. 8s (NNOTYs - (Na(B.(Nn(B.(NsKRQBINs ((NsANKT(B-(NpETERBURGs (NlANXs (NpLANETA MUZYKIs, 2020)
(NfORTEPIANNYE \T@DY sKRQBINA(B, (NNARQDU S \T@DAMI lISTA(B, (N{OPENA(B, (NsEN(B-(NsANSA I DR(B., (NSO^ETA@T INSTRUKTIWNOE ZNA^ENIE S GLUBOKIM MUZYKALXNYM SODERVANIEM(B. s
Keywords: (NFORTEPIANOs